IMPROVING VOCABULARY MEMORIZING SKILLS USING CANVA APPLICATION-BASED GRAPHIC DESIGN MEDIA OF SMA TAKHASSUS AL-QUR’AN STUDENTS - Yunianti, Febby; Purwanto, Buntara Adi (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
The importance of selecting learning media is an important support to minimize the ineffectiveness of the classroom atmosphere to be fun and not boring, especially in mastering english vocabulary. This was a CAR with qualitative approach which consists of 4 stages, namely planning, implementation, observation, and reflection. the sample taken is class XI H at SMA Takhassus AL-Quran. The instruments used in this research namely, observation checklist, test, interview and documentation. The results showed that Canva application based graphic design media can improve students' vocabulary mastery based on checklist observation data increased from 33.7% to 63.7% in cycle I and in cycle 2 to 88.75%. Vocabulary test data increased from an average of 70.7% to 74% in Cycle I and to 86% in Cycle 2. The improvement in the interview can be seen from the responses to each question, which indicate that Canva's application media can increase students' motivation in learning English, especially in mastering English, and is very efficient to use in learning. From the above data, it can be concluded that the use of Canva application based graphic design media can improve students' vocabulary mastery.